The elements a very short introduction - Ball, Philip 1962- (Very short introductions, 2004)
"This Very Short Introduction traces the history and cultural impact of the elements on humankind, and examines why people have long sought to identify the substances around them. Looking beyond the Periodic Table, the author examines our relationship with matter, from the uncomplicated vision of the Greek philosophers, who believed there were four elements - earth, air, fire, and water - to the work of modern-day scientists in creating elements such as hassium and meitnerium. Packed with anecdotes, The Elements is a highly engaging and entertaining exploration of the fundamental question: what is the world made from?"--BOOK JACKET.